Yield stability of brazilian wheat varieties - Osorio, E.A. (Pesquisa Agropecuaria Brasileira, 2014)
Nineteen Brazilian wheat varieties have been tested as to their yielding stability, through the linear regression method, using experimental data recorded at six Rio Grande do Sul localities, from 1975 to 1979. The regression coefficient analysis of grain yield in relation to the environment quality showed that the tested varieties, except IAS - 62, were adjusted to the middle regression and almost all of them reacted similarly to the environment variations. Most of the varieties have shown similar performance under variable environmental conditions, however some of them (IAS 55, IAS 58, IAS 61, Jacuí and Nobre) performed poorly as evidenced by significant regression deviations.